Sense of Place in the Tourist Area of Seumadu Beach, Lhokseumawe City - Annisa Zuhra; Yenny Novianti; Eri Saputra (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Research on the sense of place in public spaces based on visitors' perceptions is essential to understand whether visitors feel an emotional attachment to the tourist area of Seumadu Island Beach. This aims to measure the strength of visitors' feelings when in the area and identify the factors shaping those feelings. This study focuses on the primary question of how the sense of place is formed in the Seumadu Island Beach tourist area and what factors influence visitors’ attachment to it as a public space. This research employs a quantitative method. The analysis results regarding sense of place show that 63.2% of respondents agree that they feel attached to this area. The strongest contributing factor to sense of place is place identity (67%), which includes aspects such as memories associated with objects and the desire to stay. This is followed by place dependence (67%), which involves aspects like the desire to revisit and fulfill certain needs, and finally, place attachment (66%), the lowest, especially in terms of safety and comfort. It can be concluded that the Seumadu Island Beach tourist area has a sense of place that is felt by its visitors or users. The primary factors influencing the sense of place in the Seumadu Island Beach area are place identity and place dependence, with place attachment in the final position.